Pengaruh Pembelajaran E-Learning dan Kualitas E-Learning Terhadap Mutu Belajar Mahasiswa Akuntansi (Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis Unisma Jurusan Akuntansi Angkatan Tahun 2017, 2018 dan 2019) - Muhammad Rizki Algadri; Junaidi Junaidi; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study discusses the effect of e-learning and the quality of e-learning on the quality of student learning. the type of research used is quantitative with the sampling method using the solvin formula and using the data collection method through questionnaires distributed using the google form. The population in this study were students at the Malang Islamic University majoring in accounting, class of 2017, 2018, 2019. The results of this study indicate that partially e-learning has an effect on the quality of student learning and the quality of e-learning has an effect on the quality of student learning. while the two variables simultaneously have a positive effect on the quality of student learning.Keywords : E-leaning learning, e-learning quality, student learning quality.